Breakup of silica agglomerates in corotating twin-screw extruder: Modeling and experiment. (October 2014) - Bumm, Sug Hun; White, James L; Isayev, Avraam I
Extensive experimental studies on silica agglomerate breakup during compounding with polymer melts of various viscosities and polarities in a modular corotating twin-screw extruder were conducted. To avoid a subjectivity of the result, due to small size particles involved, silica agglomerates were characterized by measuring their mass average values. Increasing the screw speed, melt viscosity, and silica concentration were found to increase the silica agglomerate breakup. The effect of these parameters on agglomerate breakup was ranked as follows: silica concentration > polymer viscosity ≈screw revolutions per minute (rpm). A good correlation between silica agglomerate breakage and power input was also found. Based on the experimental data and dispersion process, a composite modular kinetic model for evaluating silica agglomerate breakup during compounding in a corotating twin-screw extruder was tested. The kinetic constants of breakup and reagglomeration of silica agglomerates were calculated based on the stresses applied to the agglomerates and their cohesive strength. These constants for silica agglomerates were found to be not significantly different at high concentrations. The latter was in contrast to experimental data from available literature on compounding of calcium carbonate with polypropylene where the high reagglomeration kinetic constants of calcium carbonate in comparison with those of breakup played a major role in the agglomerate breakup. Comparison of the experimental and calculated results on the silica agglomerate size evolution during compounding with polymer melts indicated a reasonable agreement between them at high rotational speeds.